A phase II study on the neo-adjuvant combination of pazopanib and radiotherapy in patients with high-risk, localized soft tissue sarcoma. (2nd December 2021) - van Meekeren, Milan; Bovee, Judith V. M. G.; van Coevorden, Frits; van Houdt, Winan; Schrage, Yvonne; Koenen, Anne Miek; Miah, Aisha B.; Zaidi, Shane; Hayes, Andrew J.; Thway, Khin; Krol, Stijn; Fiocco, Marta; et al.
Abstract: Purpose: A prior phase I study showed that the neo-adjuvant combination of pazopanib and radiotherapy was well tolerated, and induced promising pathological responses in soft-tissue sarcoma patients. Results of the subsequent prospective, multicenter phase II, PASART-2 trial are presented here, further investigating the efficacy and safety of this combination. Patients and methods: Patients with high-risk, localized soft-tissue sarcoma received neo-adjuvant radiotherapy, 50 Gy in 25 fractions (PASART-2A) or with a subsequent dose de-escalation to 36 Gy in 18 fractions (PASART-2B). This was combined with 800 mg once daily pazopanib, which started one week before radiotherapy and finished simultaneously. After an interval of 4–8 weeks, surgical resection was performed. The primary endpoint was the rate of pathological complete responses (pCR), defined as ≤5% viable cells. Results: 25 patients were registered in the study, 21 in PASART-2A and 4 in PASART-2B. After central pathology review, the combination treatment led to a pCR in 5 patients (20%). 17 patients (68%) experienced grade 3+ toxicities during neo-adjuvant treatment, of which the most common were alanine aminotransferase (ALT) elevation, aspartate aminotransferase (AST) elevation, and hypertension, all asymptomatic. Grade 3+ acute post-operative toxicities occurred in 5 patients (20%), of which the most common was wound infection. All patients completed the full radiotherapy regimen and underwent surgery. Pazopanib was discontinued before completion in 9 patients (36%), due to elevated ALT and/or AST, and shortly interrupted in 2 patients (8%), due to hypertension. Conclusion: Apart from asymptomatic hepatotoxicity, the study regimen was well tolerated. Although the pre-specified efficacy endpoint (30% pCR) was not met, a more than doubling of historical pCR rates after neo-adjuvant radiotherapy alone was observed, which warrants further investigation.